Hayek's twin ideas: reconciling methodological individualism and group selection. (16th August 2021) - Schaefer, Alexander
Abstract: Hayek repeatedly refers to 'the twin ideas of evolution and spontaneous order'. Yet, critics argue that Hayek's theory of cultural group selection is inconsistent with his theory of spontaneous order. To assess these criticisms, this paper situates Hayek's social theory in the contemporary discussion surrounding multilevel selection. Hayek's theory posits two main levels—rules and order—that exhibit upward and downward causation. An examination of Hayek's theory of cultural group selection and his account of methodological individualism reveals that neither one can provide a fully adequate explanation of social phenomena. Neither individualistic nor group-selectionist analyses allow the theorist to fully account for social order, but taken together they provide a more complete explanation. Far from being substitutes, therefore, both types of analysis are complementary aspects of Hayek's social theory. Understanding Hayek's theory in this way allows us to glimpse how he might weigh in on contemporary debates surrounding multilevel selection in human societies.